x(23-x)=143

Simple and best practice solution for x(23-x)=143 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(23-x)=143 equation:


Simplifying
x(23 + -1x) = 143
(23 * x + -1x * x) = 143
(23x + -1x2) = 143

Solving
23x + -1x2 = 143

Solving for variable 'x'.

Reorder the terms:
-143 + 23x + -1x2 = 143 + -143

Combine like terms: 143 + -143 = 0
-143 + 23x + -1x2 = 0

Begin completing the square.  Divide all terms by
-1 the coefficient of the squared term: 

Divide each side by '-1'.
143 + -23x + x2 = 0

Move the constant term to the right:

Add '-143' to each side of the equation.
143 + -23x + -143 + x2 = 0 + -143

Reorder the terms:
143 + -143 + -23x + x2 = 0 + -143

Combine like terms: 143 + -143 = 0
0 + -23x + x2 = 0 + -143
-23x + x2 = 0 + -143

Combine like terms: 0 + -143 = -143
-23x + x2 = -143

The x term is -23x.  Take half its coefficient (-11.5).
Square it (132.25) and add it to both sides.

Add '132.25' to each side of the equation.
-23x + 132.25 + x2 = -143 + 132.25

Reorder the terms:
132.25 + -23x + x2 = -143 + 132.25

Combine like terms: -143 + 132.25 = -10.75
132.25 + -23x + x2 = -10.75

Factor a perfect square on the left side:
(x + -11.5)(x + -11.5) = -10.75

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| Logx=27.961678 | | (u-6)*9=63 | | 2(3+3v)= | | 6q+5.8=23.8 | | x-20=1+6x | | 4n-36=-8(1-4n) | | x/5-7=2q*x | | 8x+23x=240 | | 2(1+b)= | | -901x=34 | | 16x-8=8x+20 | | d(t)=340t+d(56) | | ax+3b=2f*x | | 4.1x-18.87=8.6 | | -1/2-6/5y=-2/3 | | d(t)=340t | | 2*x=24 | | -8v+44=4(v-7) | | 10-10x=-60 | | 6(u-3)=-6u+30 | | 5/6=9/x | | -4w+32=-6(w-6) | | 7+1x=2x+(-1) | | x^3-27x-12=0 | | 14(b)=a | | Y+3+3=4Y | | -5-15y+1=14y-32y | | g+2=6 | | -9=n/10 | | P/s=8 | | f(2)=6x+5 | | 2(8x-1)+7(x+5)=-99 |

Equations solver categories